Small Fiber Polyneuropathy May Be a Nexus Between Autonomic Nervous System Dysregulation and Pain in Interstitial Cystitis/Bladder Pain Syndrome - Wolff, Dylan T.; Walker, Stephen J. (Frontiers in Pain Research, 2022)
Interstitial cystitis/bladder pain syndrome (IC/BPS) is a highly heterogeneous chronic and debilitating condition which effects millions of women and men in the United States. While primarily defined by urinary symptoms and pain perceived to be emanating from the bladder, IC/BPS patients frequently have co-occurring conditions and symptoms, many of which affect diverse body systems related to autonomic nervous system function. The impact on the autonomic system appears to stem from increased sympathetic innervation of the urinary tract, along with increased systemic sympathetic tone and decreased parasympathetic tone. Concurrent with these findings is evidence for destruction of peripheral sympathetic innervation to the sweat glands which may relate to small fiber polyneuropathy. It is unknown to what degree the wider alterations in autonomic function are also related to destruction/alterations in the small fibers carrying autonomic innervation. This potential nexus is an important point of investigation to better understand the unclarified pathophysiology of interstitial cystitis/bladder pain syndrome, the numerous co-occurring symptoms and syndromes, and for the identification of novel targeted therapeutic strategies.